2002
DOI: 10.1046/j.1442-1984.2002.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Elaeagnus umbellata on a gravel bar in the Naka River, Shikoku, Japan

Abstract: The present study seeks to identify the expansion process of the shrub Elaeagnus umbellata Thunb. (Elaeagnaceae) on a gravel bar in the Naka River, Shikoku, Japan, in relation to the hydrogeomorphologic regime of the habitat. The establishment pattern was determined by a series of aerial photographs, and the establishment years were confirmed by examining tree rings taken from five different areas within the population. The topographic change of the river cross‐section was analyzed and it was found that the es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…Plant distributions in floodplains are determined not only by physiological stress due to floods but also by physical disturbance, soil water availability (Battaglia et al 2000;Hall and Harcombe 2001;Xiong et al 2003), soil nutrient content (Weiher and Keddy 1995), soil composition (Niiyama 1987), seed dispersal limitations (Kohri et al 2002), inter-specific competition (Weiher and Keddy 1995;Xiong et al 2003), and interactions among these factors (Xiong et al 2003). The three Ulmaceae species prefer moderate soil humidity and slightly xeric soil condition but can grow over a wide range of soil conditions (Higa et al 2006;Sakamoto 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant distributions in floodplains are determined not only by physiological stress due to floods but also by physical disturbance, soil water availability (Battaglia et al 2000;Hall and Harcombe 2001;Xiong et al 2003), soil nutrient content (Weiher and Keddy 1995), soil composition (Niiyama 1987), seed dispersal limitations (Kohri et al 2002), inter-specific competition (Weiher and Keddy 1995;Xiong et al 2003), and interactions among these factors (Xiong et al 2003). The three Ulmaceae species prefer moderate soil humidity and slightly xeric soil condition but can grow over a wide range of soil conditions (Higa et al 2006;Sakamoto 2009).…”
Section: Discussionmentioning
confidence: 99%
“…japonica and A. aspera are ornithochory species. Kohri et al (2002) reported that berries of riparian tree species were widely dispersed on a floodplain by floods. Hence, it is unlikely that the seed dispersal of these Ulmaceae species is restricted in the upper areas of floodplains.…”
Section: Discussionmentioning
confidence: 99%
“…These results have clarified that an increase in suitable habitat itself within the river system has increased the number of E. umbellata communities, as they tend to distribute on elevated terraces with coarse bed materials in the gravel bars in the Yoshino River (Kohri et al . 2000; Kohri 2008) and Naka River (Kohri et al . 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Elaeagnus umbellata is highly heliophytic and does not appear as a result of succession, but rather tends to establish linear‐form colonies on bare gravel bars after experiencing late autumnal floods. It does not form a permanent seed bank (Nakagoshi 1985), a gap detection habit is not present, and all seeds germinate only in spring (Kohri et al . 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation